2004
DOI: 10.1167/iovs.03-0932
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metalloprotease Inhibitors on Corneal Allograft Survival

Abstract: MMP inhibitor treatment of cornea-derived endothelial cells results in increased FasL expression and function. MMP inhibitor treatment prolongs corneal allograft survival and results in a modest increase in corneal allograft acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“…MMP-2, together with MMP-9, degrades basement membrane components such as collagen IV, and is now extensively studied in the eye tissue (Sivak and Fini, 2002). Through numerous studies of MMP-2 and MMP-9, many investigators have shown that in corneal lesions such as keratitis (Yang et al, 2003;Xue et al, 2003), corneal alkali burn (Zhang et al, 2002;Barros et al, 2007), and corneal transplant rejection (Stuart et al, 2004), the expression levels and activities of MMP-2 and MMP-9 are increased, and they are considered the main factors contributing to these pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2, together with MMP-9, degrades basement membrane components such as collagen IV, and is now extensively studied in the eye tissue (Sivak and Fini, 2002). Through numerous studies of MMP-2 and MMP-9, many investigators have shown that in corneal lesions such as keratitis (Yang et al, 2003;Xue et al, 2003), corneal alkali burn (Zhang et al, 2002;Barros et al, 2007), and corneal transplant rejection (Stuart et al, 2004), the expression levels and activities of MMP-2 and MMP-9 are increased, and they are considered the main factors contributing to these pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the concentration of a1-antitrypsin in aqueous humour cannot be used as a prognostic indicator at the time of corneal rejection. Interestingly, it has been suggested that certain metalloproteinase activity is equal to serine proteinase activity (Ando et al 1993), and it has been shown that metalloproteinase inhibitor treatment prolongs corneal allograft survival and results in a modest increase in corneal allograft acceptance in a mouse model (Stuart et al 2004). In perspective, our findings could lead to a new treatment of corneal rejection with local use of a1-antitrypsin augmentation therapy in the anterior chamber.…”
Section: Discussionmentioning
confidence: 59%
“…Penetrating keratoplasties were performed with minor modification from previously published methods 21 . In summary, Provisc (Alcon Laboratories, Fort Worth, TX) was injected into the anterior chamber of the eye of an anesthetized donor.…”
Section: Methodsmentioning
confidence: 99%